Analysis of Students' Environmental Care Attitudes at SDIT AL-IRSYADIYYAH - Haerudin; Yulistina Nur DS; Urwatil Wusko (LPPM Universitas Buana Perjungan Karawang, 2020)
This study aims to determine how much environmental care students in elementary schools are and the researchers hope to foster a sense and love of caring for the school environment. This research uses a descriptive qualitative approach. This type of research uses observation, interviews and documentation. The place for the implementation of this research is SDIT Al-Irsyadiyyah, Telukjambe Timur District, Karawang Regency. The subjects of this research are the principal, teachers and students. The results of this study indicate that students of SDIT Al-irsyadiyyah, Telukjambe District show that environmental care at school is carried out through routine school activities, spontaneous activities, modeling and conditioning. Environmental care activities require that every morning and after school clean the environment at school besides that there are routine activities, namely Jumsih (clean Friday) which all involve school members including school principals, teachers and students who always play an active role in this activity. In this case there is a sanction for students and teachers who do not carry out the morning picket.